Cultural representation and intercultural interaction in textbooks of English as an international language - Tomy Kartika Putra; Dewi Rochsantiningsih; Slamet Supriyadi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
The present study attempts to scrutinize the manifestation of cultures and intercultural interactions in English textbooks. It investigates three English textbooks for twelfth-grade students produced by three relatively major publishers in Indonesia by employing cultural content and intercultural interaction analysis. The findings show that the examined textbooks do not appropriately demonstrate cultural diversity in the international context as cultures of Indonesia and English-speaking countries have their dominancy. Also, the textbooks mostly demonstrate intercultural interactions in fragmented, limited, and superficial ways. Some recommendations are addressed for future textbooks authors and publishers as well as English teachers. The results suggest textbook publishers and authors include more the material about international culture and to provide more the demonstration of deep intercultural interaction. Moreover, teachers need to be creative by adding supplementary cultural materials to patch up the shortcomings of the textbooks.